(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
The global escalation of morbid obesity has established bariatric surgery as the gold standard for long-term weight loss and metabolic improvement. A significant proportion of bariatric candidates present with concomitant surgical pathologies, most notably cholelithiasis and abdominal wall hernias. The decision to perform simultaneous (concomitant) procedures-combining bariatric surgery with another surgical intervention-remains a subject of intense debate among surgeons. Proponents argue for the benefits of a single anesthetic episode and cost-effectiveness, while critics highlight concerns regarding increased operative time, infectious risks, and perioperative complications. This review examines the current evidence regarding the safety, feasibility, and clinical outcomes of simultaneous bariatric procedures.